A flexible and wearable epidermal ethanol biofuel cell for on-body and real-time bioenergy harvesting from human sweat. (August 2021) - Sun, Mimi; Gu, Yanan; Pei, Xinyi; Wang, Jingjuan; Liu, Jian; Ma, Chongbo; Bai, Jing; Zhou, Ming
Abstract: Flexible and wearable epidermal biofuel cells (BFCs) that are worn on skin for the direct electricity generation from human perspiration are perceived to be a most enticing and promising next-generation energy source for addressing the on-body energy-harvesting challenge of wearable electronics. Previously reported epidermal BFCs are only focused on the utilization of human endogenous substances ( i.e ., glucose or lactate that can be produced by human body) in sweat as the biofuels for power production. Given the substances diversity in human body, some exogenous substances (that cannot be produced by body) are abundant in sweat in certain daily situations, however, their utility for epidermal bioenergy harvesting has been ignored so far. In the present work, we propose the first example of a flexible and wearable epidermal microfluidic human exogenous substance ethanol/oxygen BFC for the simultaneous sweat sampling and sweat bioelectricity generation on skin of individuals who drink alcohol. Certain actual situations that were associated with alcohol absorption and elimination in human body were considered and investigated for skin-on, continuous in situ sweat ethanol bioenergy generation in controlled environments. Such non-invasive flexible and wearable epidermal ethanol BFC expands the scope of human sweat-derived biofuels from endogenous substances to exogenous ones and holds great promise for the skin-worn and real-time bioenergy harvesting from human perspiration, which may open up a new challenge and approach to explore the human sweat for bioenergy conversion. Graphical Abstract: We demonstrated the first example of a flexible and wearable epidermal microfluidic human exogenous substance ethanol/oxygen biofuel cell through a skin-worn, real-time in situ fashion to harvest the continuous electrical power from alcohol drinkers' perspiration in different real-life scenarios. ga1 Highlights: The first example of a flexible and wearable epidermal human exogenous substance ethanol biofuel cell. The simultaneous sweat sampling and sweat bioelectricity generation on skin of individuals who drink alcohol. Certain actual situations were considered and investigated for skin-on, continuous in situ sweat ethanol bioenergy generation.